Cultural adaptation of the Test of Narrative Language (TNL) into Brazilian Portuguese - Rossi, Natalia Freitas [UNESP]; Lindau, Tâmara de Andrade; Gillam, Ronald Bradley; Giacheti, Célia Maria [UNESP] (My University, 2016)
Purpose: To accomplish the translation and cultural adaptation of the Test of Narrative Language (TNL) into Brazilian Portuguese. Methods: The TNL is a formal instrument which assesses narrative comprehension and oral narration of children between the ages of 5-0 and 11-11 (years-months). The TNL translation and adaptation process had the following steps: (1) translation into the target language; (2) summary of the translated versions; (3) back-translation; (4) checking of the conceptual, semantics and cultural equivalence process and (5) pilot study (56 children within the test age range and from both genders). Results: The adapted version maintained the same structure as the original version: number of tasks (both, three comprehension and oral narration), narrative formats (no picture, sequenced pictures and single picture) and scoring system. There were no adjustments to the pictures. The McDonald's Story was replaced by the Snack Bar History to meet the semantic and experiential equivalence of the target population. The other stories had semantic and grammatical adjustments. Statistically significant difference was found when comparing the raw score (comprehension, narration and total) of age groups from the adapted version. Conclusion: Adjustments were required to meet the equivalence between the original and the translated versions. The adapted version showed it has the potential to identify differences in oral narratives of children in the age range provided by the test. Measurement equivalence for validation and test standardization are in progress and will be able to supplement the study outcomes.
Keywords: Adaptation; Child language; Language tests; Narration; Translation